Effects of dibutyl phthalate and di (2-ethylhexyl) phthalate on hepatic structure and function of adult male mice. (August 2022) - Batool, Saira; Batool, Sajida; Shameem, Sitara; Batool, Tahira; Batool, Saima
The objective of the present research was to determine if dibutyl phthalate (DBP) and di-(2-ethylhexyl) phthalate (DEHP) alone and combined exposure induced pathological alterations in laboratory reared albino mice. Adult male mice were equally divided (n = 10) into Control, corn oil (CO), DBP, DEHP, and DBP+DEHP treated groups. Dibutyl phthalate (250 mg/kg), DEHP (300 mg/kg), and DBP+DEHP (250+300 mg/kg), respectively, were administered by oral gavage mixed in corn oil (0.2 mL) for 28 days. All animals were sacrificed following 28 days of treatment and blood was collected for serum lipid profiles and liver function tests. Liver samples were also collected for observation of histological changes. Microphotographs of hematoxylin and eosin-stained sections were used for computer-based micrometry. CO, DBP, DEHP, and DBP+DEHP treatment resulted in a significant increase in the mean body and liver weights as compared with the Control group. Histological examination of the livers with DBP and/or DEHP treatment showed marked alterations leading to hepatic hypertrophy. In the treated groups, a significant increase in the mean number of mononucleated, binucleated cells, and oval cells per unit area was noticed with disorganized trabecular arrangement as compared with the Control group. Treatment with DBP and/or DEHP resulted in large regeneration zones in the liver and an increased relative nucleo-cytoplasmic index of mononuclear shepatocytes when compared with the Control group. All treatments caused a significant increases in the liver enzymes and proteins as well as altered serum cholesterol, triglycerides, LDL, and VLDL levels. The histopathological and serological findings confirmed the toxic potentials to hepatic tissue of DBP and DEHP either given alone or in combination.